Gene cluster for streptomycin biosynthesis in Streptomyces griseus: nucleotide sequence of three genes and analysis of transcriptional activity. - Distler, J (1987)
Three streptomycin (SM) production genes from Streptomyces griseus clustered around aphD, the major resistance gene, have been sequenced: strB, coding for an aminocyclitol amidinotransferase, ORF5 (strR), a putative regulatory gene, and ORF1 (strD), possibly coding for a hexose nucleotidylating enzyme. Three promoters and at least five, partially overlapping, transcripts have been identified by S1 mapping and Northern blot experiments. aphD, the resistance gene, is transcribed from two promoters. One of them, located inside the strR gene, seems to be constitutive and the other is switched on later in the growth phase. The late transcripts cover the resistance gene (aphD) and a regulatory gene (strR) which controls the expression of strB.